Multi-level planning and integrated rural development in India - Misra, R. P. (New Delhi, 1980)
It is well known that literature on multi-level planning is quite limited. With the current emphasis on decentralised planning and rural development, several issues touching on multi-level planning-concepts, methodologies as well as operational procedures are exercising the minds of researchers, planners and administrators. The present book is a modest contribution. to this end. It is based on papers and articles contributed by the authors over the last five years. The individual papers go into depth on selected issues. They reveal the authors' percep tions of the spatial, economic and political dimensions of the subject.
Keywords: Economic development